Comparison of Clinical and Functional Outcome of Cold Steel Dissection versus Coblation Technique in Tonsillectomy - Regmi, Deepak; Bista, Meera; Shrestha, Sangita (Journal of Nepal Health Research Council, 2022)
Background: To ameliorate the intra and post-op morbidities associated with newer techniques for tonsillectomy like coblation has been introduced in the recent past. This study was aimed to compare the cold steel dissection with the coblation technique with regards to its effectiveness and safety.Methods: An observational comparative study was carried out in 90 patients undergoing tonsillectomy between July 2018 to December 2019. Forty-five patients in each group of cold steel dissection and coblation were compared between the operative time, intraoperative blood loss, post-operative pain, post-operative bleeding and return to work. Intraoperative blood loss was measured using a standard sized gauge piece whereas post-operative pain was measured using a visual analogue scale (0-10) at first and third day of surgery. Results: The age and sex were comparable between the groups. The mean operation time (31.40±4.52 min versus 17.02±3.11 min), intraoperative blood loss (27.20±7.16 ml vs 9.73±5.52 ml), post-operative pain in day 1 (8.02±1.27 vs 4.98±1.03), post-operative pain in day 3 (4.80±0.89 vs 2.76±0.74) and time needed to return to work in days (10. 31±1.29 vs 6.76±1.20) were statistically significant in coblation group (p<0.000). Primary and secondary post-operative haemorrhage rates were similar in both the groups. There was no return to theatre for hemostasis.Conclusions: Coblation tonsillectomy significantly reduces operation time, intraoperative blood loss, post-operative pain (day1 and 3) and time required to return to work . This technique doesn’t differ from cold steel dissection tonsillectomy in terms of primary and secondary post-operative hemorrhage.Keywords: Coblation, cold dissection, tonsillectomy